“As a teacher, I think that you can feel really alone if you haven't got other people around to support…”: School staff experiences of participating in a group consultation model to support primary aged pupils with Social, Emotional and Mental Health (SEMH) needs. - Dhaliwal, Amandeep (2024)
Background: The increasing prevalence of social, emotional and mental health (SEMH) needs among children and young people (CYP) (NHS England, 2023) and the subsequent pressures on school staff to provide adequate support (Lowry et al., 2022) highlight the necessity for more effective SEMH interventions. A systematic review of the literature suggests there is a scarcity of research exploring school staff experiences with group consultation models for supporting CYP with SEMH needs. Although Newton and Wilson’s (2013) Insights and Solutions Circles (ISCs) are utilised by Educational Psychologists (EPs), there remains a gap in understanding school staff's real-life experiences with this consultation model.